Geminin ablation in vivo enhances tumorigenesis through increased genomic instability. Issue 2 (21st August 2018) - Champeris Tsaniras, Spyridon; Villiou, Maria; Giannou, Anastassios D; Nikou, Sofia; Petropoulos, Michalis; Pateras, Ioannis S; Tserou, Paraskevi; Karousi, Foteini; Lalioti, Maria‐Eleni; Gorgoulis, Vassilis G; Patmanidi, Alexandra L; Stathopoulos, Georgios T; et al.
Abstract: Geminin, a DNA replication licensing inhibitor, ensures faithful DNA replication in vertebrates. Several studies have shown that geminin depletion in vitro results in rereplication and DNA damage, whereas increased expression of geminin has been observed in human cancers. However, conditional inactivation of geminin during embryogenesis has not revealed any detectable DNA replication defects. In order to examine its role in vivo, we conditionally inactivated geminin in the murine colon and lung, and assessed chemically induced carcinogenesis. We show here that mice lacking geminin develop a significantly higher number of tumors and bear a larger tumor burden than sham‐treated controls in urethane‐induced lung and azoxymethane/dextran sodium sulfate‐induced colon carcinogenesis. Survival is also significantly reduced in mice lacking geminin during lung carcinogenesis. A significant increase in the total number and grade of lesions (hyperplasias, adenomas, and carcinomas) was also confirmed by hematoxylin and eosin staining. Moreover, increased genomic aberrations, identified by increased ATR and γH2AX expression, was detected with immunohistochemistry analysis. In addition, we analyzed geminin expression in human colon cancer, and found increased expression, as well as a positive correlation with ATM/ATR levels and a non‐monotonic association with γH2AX. Taken together, our data demonstrate that geminin acts as a tumor suppressor by safeguarding genome stability, whereas its overexpression is also associated with genomic instability. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.